Zinc supplementation for prevention and management of recurrent aphthous stomatitis: a systematic review - Halboub, Esam; Al-Maweri, Sadeq A.; Parveen, Sameena; Al-Wesabi, Mohammed; Al-Sharani, Hesham Mohammed; Al-Sharani, Amani; Al-Kamel, Ahlam; Albashari, Abdullkhaleg; Shamala, Anas (Elsevier, 2021)
Background Recurrent aphthous stomatitis (RAS) is a very common oral ulcerative disease with no definitive cure. Growing evidence suggests a significant association between zinc deficiency and RAS. Objectives To assess the efficacy of systemic zinc supplementations in the prevention and management of RAS. Methods Five databases were searched for all English and Chinese studies published up to November 2020. All clinical trials that assessed the efficacy of zinc supplementations in the management and/or prevention of RAS were included. Results Seven clinical trials comprising 482 RAS patients (250 in zinc group) fulfilled the inclusion criteria. The follow-up period ranged from three months to one year. Five studies showed significantly better efficacy of zinc in reducing the recurrence rates of RAS, whereas two studies did not report any significant differences compared to the controls. Four studies reported on signs/symptoms of RAS, three of which showed superior outcomes in favour of zinc, while one study reported comparable results. Conclusion Zinc supplementation seems to be efficacious in the management and prevention of RAS. However, further clinical trials with standardized methodologies and adequate follow-up periods are required to confirm the efficacy of zinc supplementations.